A case of a long-term survival achieved by surgical treatment and chemotherapy for late recurrence of AFP-producing gastric cancer - Manabu Harada; Hironori Tsujimoto; Takashi Ichikura; Hiromi Nagata; Nozomi Ito; Shinsuke Nomura; Hiroyuki Horiguchi; Yoshihisa Yaguchi; Yoji Kishi; Hideki Ueno (Surgical Case Reports)
Abstract Background Alpha-fetoprotein-producing gastric cancer (AFP-GC) is a relatively rare disease, with a dismal prognosis. Case presentation We report the case of a patient with long-term survival after surgery for the recurrence of AFP-GC. A 71-year-old man was diagnosed with gastric cancer and underwent distal gastrectomy with D2 lymphadenectomy (pT3N2M0). Pathological examination of the resected specimen revealed AFP-GC. Fifteen years after the gastrectomy, the patient experienced anorexia and was admitted with a mass located at the mesentery of the small intestine. Following a diagnosis of gastrointestinal stromal tumor of the mesentery, a tumor resection with partial small intestine was performed. The final histopathological diagnosis was AFP-GC’s recurrence in the small-bowel mesentery. Two months later, multiple liver metastases were identified, and serum AFP level was found to be extremely high (17,447 ng/mL). Chemotherapy with S-1+CDDP (SP) was initiated for liver metastasis. However, owing to anorexia and fatigue, SP therapy was discontinued following the patient’s request at the end of two courses. A CT scan at 1 month after the discontinuation of chemotherapy did not reveal liver metastasis, and serum AFP level decreased to the normal range. He is alive at present with no re-recurrence and no elevation of serum AFP level at 7 years after the second surgery without any chemotherapy. Conclusion Even if recurrence of AFP-GC is diagnosed, radical resection and chemotherapy are effective, as noted in the present case.